2020
DOI: 10.1002/ajmg.a.61492
|View full text |Cite
|
Sign up to set email alerts
|

KPTN gene homozygous variant‐related syndrome in the northeast of Brazil: A case report

Abstract: Alteration of the KPTN gene, responsible for the coding of kaptin (a protein involved in actin cytoskeletal dynamics), causes a syndrome characterized by macrocephaly, neurodevelopmental delay and epileptic seizures. We report the first Brazilian case of KPTN gene variation, previously described in nine subjects from four interlinked families from an Amish community in Ohio, two Estonian siblings and a 9‐year‐old boy from Kansas City. We report a case of KPTN‐related syndrome in a 5‐year‐old child which presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…We report two female Spanish siblings, homozygous for a dinucleotide duplication at Chr19:47984018_47984019dup (hg19): NM_007059.3: c.597_598dup p.(Ser200Ilefs*55) in the KPTN gene. The same variant has already been described by Lucena et al (2020) in a Brazilian girl.…”
supporting
confidence: 78%
See 4 more Smart Citations
“…We report two female Spanish siblings, homozygous for a dinucleotide duplication at Chr19:47984018_47984019dup (hg19): NM_007059.3: c.597_598dup p.(Ser200Ilefs*55) in the KPTN gene. The same variant has already been described by Lucena et al (2020) in a Brazilian girl.…”
supporting
confidence: 78%
“…Interestingly, both siblings in the present report showed delayed anterior fontanel closure. The younger sister also showed brain anomalies, as did patient 5 reported by Baple et al (2014) and two additional patients reported by Thiffault et al 2020 (Baple et al, 2014;Pajusalu et al, 2015;Thiffault et al, 2020;Lucena et al, 2020), but no information was provided regarding the age of onset of the metabolic or endocrine problems. Although our patients did not present behavioral, endocrinological or metabolic alterations, or seizures at the time of this study, they are still fairly young and these aspects need to be followed up closely.…”
mentioning
confidence: 88%
See 3 more Smart Citations